2023
DOI: 10.1021/acs.jafc.2c09108
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Biosynthesis of 2-Keto-4-hydroxybutyrate from Cheap C1 Compounds Using Rationally Designed Pyruvate Aldolase and Methanol Dehydrogenase

Abstract: One-carbon chemicals (C 1s) are potential building blocks as they are cheap, sustainable, and abiotic components. Methanol-derived formaldehyde can be another versatile building block for the production of 2-keto-4-hydroxyacid derivatives that can be used for amino acids, hydroxy carboxylic acids, and chiral aldehydes. To produce 2-keto-4-hydroxybutyrate from C 1s in an environment-friendly way, we characterized an aldolase from Pseudomonas aeruginosa PAO1 (PaADL), which showed much higher catalytic activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Specifically, KHB aldolase has the potential to shift sugar-based metabolism toward industrially favorable biomanufacturing. This is due to the ability of KHB aldolase to catalyze the condensation of formaldehyde and pyruvate to form 2-keto-4-hydroxybutyrate, a vital building block for the synthesis of industrial intermediates such as l -homoserine and 1,3-propanediol . These intermediates can then be used to construct large carbon molecules of industrial value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, KHB aldolase has the potential to shift sugar-based metabolism toward industrially favorable biomanufacturing. This is due to the ability of KHB aldolase to catalyze the condensation of formaldehyde and pyruvate to form 2-keto-4-hydroxybutyrate, a vital building block for the synthesis of industrial intermediates such as l -homoserine and 1,3-propanediol . These intermediates can then be used to construct large carbon molecules of industrial value.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the ability of KHB aldolase to catalyze the condensation of formaldehyde and pyruvate to form 2-keto-4hydroxybutyrate, a vital building block for the synthesis of industrial intermediates such as L-homoserine and 1,3propanediol. 37 These intermediates can then be used to construct large carbon molecules of industrial value. In contrast, the sugar compounds ribulose-5-phosphate (Ru5P) and hexose-6-phosphate (hexose-6-p) involved in Hp metabolism serve as cellular metabolism precursors in the synthesis of biological molecules such as nucleotides and nucleic acids and have limited industrial relevance.…”
Section: Design Of Artificial Methylotrophic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific activity of the enzyme was defined as the produced amount of product per unit reaction time per enzyme amount. Formaldehyde, pyruvate, and 2-KHB were quantitatively determined by high performance liquid chromatography (HPLC) as described in our previous study (Jeong et al 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported the use of pyruvate aldolase from Pseudomonas aeruginosa with maltose-binding protein (MBP-PaADL) for 2-KHB production from formaldehyde and pyruvate (Jeong et al 2023 ). In the previous study, MBP-PaADL produced the highest 2-KHB yield reported so far.…”
Section: Introductionmentioning
confidence: 99%